Issues and Ethics facing the Administration of Special Education in Nigeria - Owobi, Emmanuel Agbo; Bodang, Juliana Rotkanggmwa (NIU Journal of Humanities, 2018)
This paper looked at issues and ethics facing the administration of special education schools in Nigeria. That ethical issues in special education relate to the ways to educate students with disabilities. Meaning that issues where people struggle to figure out the right thing to do. In their discussion, the authors said that those who teach children with special needs in Nigeria schools today are face with ethical dilemmas each day in their classroom and how to respond to these dilemmas seems to be a very difficult task. They also augured that to be able to address some of these ethical issues, professional in the field of special educators need to be guided by professional ethical principles and practice standards. The author noted that for some times past the administration of special education programme was faced with lack of policy implementation and misplacement of priority. Finally, strategies for the administration of special education programme in Nigeria were detailed.